Fragmentation study of clerodane diterpenes from Casearia species by tandem mass spectrometry (quadrupole time-of-flight and ion trap) - Danuello, Amanda; Castro, Rogerio Cardoso de [UNESP]; Pilon, Alan Cesar [UNESP]; Pires Bueno, Paula Carolina; Pivatto, Marcos; Vieira Junior, Gerardo Magela; Carvalho, Flavio Alexandre [UNESP]; Oda, Fernando Bombarda [UNESP]; Perez, Consuelo Javiera; Lopes, Norberto Peporine; Dos Santos, Andre Gonzaga [UNESP]; Ifa, Demian Rocha; et al. (Wiley-Blackwell, 2020)
Rationale Clerodane-type diterpenes from Casearia species show important pharmacological activites such as antitumor, antimicrobial and anti-inflamatory. There are several mass spectrometry (MS)-based methods for identification of diterpenes; however, there is still a lack of MS procedures capable of providing characteristic fragmentation pathways for a rapid and unambiguous elucidation of casearin-like compounds. Methods Casearin-like compounds were investigated by electrospray ionization tandem mass spectrometry (ESI-MS/MS). The fragmentation studies were carried out by tandem mass spectrometry in space (quadrupole time-of-flight (QTOF)) using different collision energies and also by tandem mass spectrometry in time (QIT) by selective isolation of product ions. Results Casearin-like compounds presented a predominance of sodium- and potassium-cationized precursor ions. Both QIT and QTOF techniques provided sequential neutral losses of esters related to the R-1 to R-5 substituents linked to the nucleus of the clerodane diterpenes. The fragmentation pathway is initiated with a cleavage of the ester moieties R-2 followed by the elimination of the ester groups R-3, both losing neutral carboxylic acids. Using QIT, it was also possible to observe the cleavage of the ester groups R-1 or R-5 by MS4 experiments. Conclusions Through a rational analysis of the fragmentation mechanisms of Casearia diterpenes it was possible to suggest an annotation strategy based on the sequential cleavages of the ester groups related to the R-2, R-3 and R-5 substituents. These results will assist studies of the dereplication and metabolomics involving casearin-like compounds present in complex extracts of Casearia species.